SAT0164 The First Study of Certolizumab Pegol in Combination with Methotrexate in Dmard-Naïve Early Rheumatoid Arthritis Patients Led to Sustained Clinical Response and Inhibition of Radiographic Progression at 52 Weeks: The C-Early Randomized, Double-Blind, Controlled Phase 3 Study. (9th June 2015) - Emery, P.; Bingham, C.O.; Burmester, G.-R.; Bykerk, V.P.; Furst, D.E.; Mariette, X.; van der Heijde, D.; Tatla, D.; Arendt, C.; Mountian, I.; VanLunen, B.; Weinblatt, M.
Abstract : Background: C-EARLY is a phase 3 study in DMARD-naïve patients (pts) with early active RA. Objectives: To assess efficacy and safety of certolizumab pegol (CZP)+MTX vs placebo (PBO)+MTX treatment in inducing and maintaining sustained clinical response and inhibiting radiographic damage in DMARD-naïve pts with early active RA. Methods: Eligible pts in this multicenter, double-blind, randomized study (NCT01519791 ) were DMARD-naïve and had early, active RA:<1 year since diagnosis at baseline (BL) fulfilling 2010 ACR/EULAR criteria; ≥4 swollen and ≥4 tender joints; DAS28(ESR)≥3.2; CRP≥10mg/L and/or ESR≥28mm/hr, rheumatoid factor or ACPA positive. Pts were randomized 3:1 to CZP (400mg Wks 0, 2, 4 then 200mg every 2 wks to Wk52)+MTX or PBO+MTX. MTX was initiated at 10mg/wk and up to 25mg/wk by Wk8, maximum tolerated dose was maintained to Wk52. Primary endpoint was sustained DAS28(ESR) remission (sREM, DAS28[ESR]≤2.6 at Wk40 and Wk52) and key secondary endpoint was sustained low disease activity (sLDA) (DAS28[ESR]≤3.2 at Wk40 and Wk52). Other secondary endpoints (included in hierarchical testing) were Wk52 ACR50 response, change from BL in HAQ-DI and change from BL in van der Heijde modified total Sharp score (mTSS). Results: 660 (CZP+MTX) and 219 (PBO+MTX) pts were randomized. 655 vs 213 were included in full analysis set (FAS; pts with BL and post-BL DAS28[ESR]) and 528 vs 163 in radiographic analysis set (FAS pts with valid BL and post-BL radiographs), respectively. BL characteristics were balanced between arms. 96.5% pts had high disease activity (DAS28[ESR]>5.1), 77.8% had erosions; mean TJC and SJC 15.8 and 12.5, respectively. Mean MTX dose after Wk8 was 21.1 (CZP+MTX) and 22.3 (PBO+MTX) mg/wk. Primary (sREM) and secondary endpoints in hierarchical testing (sLDA, ACR50, HAQ-DI change from BL, mTSS change from BL) were statistically significant (Figure shows all except HAQ-DI LS mean change from BL, -1.00 vs -0.82, p<0.001). Lower Erosion Score, Joint Space Narrowing (Figure ) and higher proportion of pts with mTSS non-progression (70.3% vs 49.7%) were seen with CZP+MTX vs PBO+MTX. AE incidence rates were similar for both arms. Infections were higher with CZP+MTX (71.8 [CZP+MTX] vs 52.7 [PBO+MTX]/100 pt-yrs), but similar for serious infections (3.3 vs 3.7/100 pt-yrs). 2 deaths were reported with CZP+MTX (1 stroke; 1 systemic tuberculosis); 1 with PBO+MTX (respiratory failure). No new safety signals for CZP were reported. Conclusions: This first report of efficacy and safety of CZP+MTX in DMARD-naïve early RA showed CZP+MTX resulted in more pts in sREM and sLDA; greater improvements in RA signs and symptoms including physical function; and inhibition of structural damage compared with PBO+MTX. Safety profile of CZP+MTX was similar to PBO+MTX. Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: P. Emery Consultant for: Pfizer, MSD, AbbVie, UCB Pharma, Roche and BMS, Speakers bureau: Pfizer, MSD, AbbVie, UCB Pharma, Roche and BMS, C. Bingham: None declared, G.-R. Burmester: None declared, V. Bykerk: None declared, D. Furst Grant/research support from: Abbott, Actelion, Amgen, Bristol-Myers Squibb, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB Pharma, Consultant for: Abbott, Actelion, Amgen, Bristol-Myers Squibb, BiogenIdec, Janssen, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB Pharma, Speakers bureau: Abbott, Actelion, UCB Pharma, X. Mariette Grant/research support from: Pfizer, Roche, Consultant for: BMS, GSK, Pfizer, Roche, UCB Pharma, D. van der Heijde Grant/research support from: AbbVie, Amgen, AstraZeneca, Augurex, BMS, Boehringer Ingelheim, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli-Lilly, Galapagos, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, UCB Pharma, Vertex, Consultant for: AbbVie, Amgen, AstraZeneca, Augurex, BMS, Boehringer Ingelheim, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli-Lilly, Galapagos, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, UCB Pharma, Vertex, D. Tatla Employee of: UCB Pharma, C. Arendt Employee of: UCB Pharma, I. Mountian Employee of: UCB Pharma, B. VanLunen Employee of: UCB Pharma, M. Weinblatt Grant/research support from: Bristol Myers Squibb, Crescendo Bioscience, UCB Pharma, Consultant for: Amgen, Abbvie, Bristol Myers Squibb, Crescendo Bioscience, UCB Pharma, Roche